2016
DOI: 10.1002/asna.201512266
|View full text |Cite
|
Sign up to set email alerts
|

Radio properties of the γ ‐ray emitting CSO candidate 2234+282

Abstract: Most of the γ-ray emitting active galactic nuclei (AGN) are blazars, although there is still a small fraction of non-blazar AGN in the Fermi/LAT catalog. Among these misaligned γ-ray-emitting AGN, a few can be classified as Compact Symmetric Objects (CSOs). In contrast to blazars in which γ-ray emission is generally thought to originate from highly beamed relativistic jets, the source of γ-ray emission in unbeamed CSOs remains an open question. The rarity of the γ-ray emitting CSOs is a mystery as well. Here w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Only recently, Migliori et al (2016) reported of the first detection of an established CSO/GPS, PKS 1718-649. This result follows the discussions of a few γ-ray CSOcandidates detected by Fermi/LAT (see also D'Ammando et al 2016, for a summary): 4C+55.1 (McConville et al 2011), PKS 1413+135 (Gugliucci et al 2005), 2234+282 (An et al 2016), and PMN J1603-4904 (Müller et al 2014).…”
Section: Introductionsupporting
confidence: 87%
“…Only recently, Migliori et al (2016) reported of the first detection of an established CSO/GPS, PKS 1718-649. This result follows the discussions of a few γ-ray CSOcandidates detected by Fermi/LAT (see also D'Ammando et al 2016, for a summary): 4C+55.1 (McConville et al 2011), PKS 1413+135 (Gugliucci et al 2005), 2234+282 (An et al 2016), and PMN J1603-4904 (Müller et al 2014).…”
Section: Introductionsupporting
confidence: 87%
“…High resolution VLBI spectral imaging observations are needed to determine the nature of those objects, which has been done in the case of 2234+282 (An et al 2016). However no convincing CSO γ-ray emitter has been found to date at redshifts beyond z>0.006.…”
Section: Empty Fieldsmentioning
confidence: 99%
“…2234 + 282 (CTD 135): An et al (2016) have claimed this BL Lac to be a compact symmetric object with a two-sided jet, based on a comparison of VLBA maps at 8.4 and 15 GHz. However, the angular resolution is insufficient to determine a spectral index for the putative core feature.…”
mentioning
confidence: 99%